Daily Variations of Temperature and Wind Speed in the Surface Boundary layer at Mizuho Station, East Antarctica - Wada, Makoto; Yamanouchi, Takashi; Mae, Shinji; Kosha, Mitsuyuki (1981)
P(論文) Micrometeorological observations at Mizuho Station were carried out from February 1979 to January 1980 by the members of the 20th Japanese Antarctic Research Expedition (JARE-20) and will be continued until January 1982 by other JARE members. Characteristics profiles of temperature, wind and net radiation during all four seasons measured simultaneously on a 30m tower are discussed in relation to the variation of net radiation. Especially, in winter, there is little variation of net radiation temperature or wind speed. In the lowest 30m layer, stratification is usually stable. On the other hand, as the snow surface is warmed by the shortwave radiation in the summer season, the temperature shows a daily variation and the wind speed also shows a daily variation. The inversion layer gradually disappeared and unstable stratification occurred in the daytime. departmental bulletin paper